Stoke-Adams syndrome interesting clinical and pathologic findings - Odriozola, Ernesto (1920)
Some of you know if we will now occupy. It has made memorable not only for the exciting and primitively misleading statements that were stated in his brief stay in this room, but for the truly unusual phenomena that all could see and especially for the originality of the changes we have been surprised at autopsy . Issues like this are not seen but rarely in life and for this reason, I wanted to collect all the elements that allow it to do a complete study.